2020
DOI: 10.1038/s41598-020-64797-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic depletion of gut microbial consortia, but not individual antibiotics, reduces amyloidosis in APPPS1-21 Alzheimer’s transgenic mice

Abstract: In preceding efforts, we demonstrated that antibiotic (ABX) cocktail-mediated perturbations of the gut microbiome in two independent transgenic lines, termed APPSWE/PS1ΔE9 and APPPS1-21, leads to a reduction in Aβ deposition in male mice. To determine whether these observed reductions of cerebral Aβ amyloidosis are specific to any individual antibiotic or require the synergistic effects of several antibiotics, we treated male APPPS1-21 transgenic mice with either individual ABX or an ABX cocktail and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…The antibiotics treatment regimen differed from the here used one (containing 1 mg/mL vancomycin, 1 mg/mL cefoxitin, 1 mg/mL gentamicin and 1 mg/mL metronidazol for two months). As an investigation in APP/PS1 mice demonstrated, however, a single administered antibiotic drug is not effective, but rather a mixture is [ 63 ]. This study also reported that only minor amounts of the administered drugs could be found in brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotics treatment regimen differed from the here used one (containing 1 mg/mL vancomycin, 1 mg/mL cefoxitin, 1 mg/mL gentamicin and 1 mg/mL metronidazol for two months). As an investigation in APP/PS1 mice demonstrated, however, a single administered antibiotic drug is not effective, but rather a mixture is [ 63 ]. This study also reported that only minor amounts of the administered drugs could be found in brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in APP/PS1 transgenic mice has found that the gut microbiota alterations with enrichment of inflammation-related bacterial taxa including Escherichia-Shigella, Desulfovibrio, Akkermansia, and Blautia precede the development of key pathological features of AD, including amyloidosis and plaquelocalized neuroinflammation (Chen Y. et al, 2020). Dodiya et al (2020) also found that synergistic alterations in the gut microbial consortia, rather than individual antimicrobial agents, underlie the observed reductions in brain amyloidosis in APPPS1-21 AD transgenic mice. Sun et al (2020c) used a novel dementia mouse model to study the influence of gut Aβ on CNS histopathology and function.…”
Section: Alterations In Gut Microbiota In Patients With Admentioning
confidence: 97%
“…These findings are congruent with previous studies that administered an antibiotic cocktail to transgenic APP/PS1 AD mice and showed a reduction in Aβ plaque pathology and plaque-associated microgliosis as well as increased cytokine and chemokine circulation (Minter et al, 2016 , 2017 ; Harach et al, 2017 ; Dodiya et al, 2019 ). Though recent literature notes that the reduced plaque deposition trends previously established in two transgenic APP/PS1 mice were only replicable when administered an antibiotic cocktail and that individual antibiotic did not affect cerebral Aβ amyloidosis (Dodiya et al, 2020 ). AD pathology was also curtailed in 5xFAD mice through the dietary supplementation of β-hydroxybutyrate (BHB), a ketone body produced during ketogenesis, which reduced Aβ plaque formation, microgliosis, and Asc speck formation (Shippy et al, 2020 ).…”
Section: Microbiome Influences On Microglia and Astrocyte Function In Neurodegenerative Diseasementioning
confidence: 99%